2010
DOI: 10.4034/1519.0501.2010.0102.0004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Health Status as an Indicator of Disease Progression in HIV Positive Children

Abstract: RESUMO ABSTRACT DESCRITORESHIV; Contagem de linfócito CD4; Síndrome de Imunodefi ciência Adquirida; Saúde bucal. KEYWORDSHIV; CD4 Lymphocyte count; Acquired Immunodefi ciency Syndrome; Oral health. ISSN -1519-0501 DOI: 10.4034/1519.0501.2010 Objecti ve: To evaluate the oral health status i.e., gingival conditi on, dental caries, oral mucosal lesions progression in a group of HIV positi ve children in relati on to CD4 count. Method: A total of 234 HIV positi ve children in the age group of 2-15 years were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a similar study conducted by Damle et al (2010) to evaluate the oral health status as an indicator of disease progression in HIV positive children, they concluded that oral health status in HIV children deteriorated with the decline in CD4 counts. It should be noted that regular dental care in HIV infected individuals result in better oral health with no greater cost than regular attendance (Hastreiter and Jiang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Damle et al (2010) to evaluate the oral health status as an indicator of disease progression in HIV positive children, they concluded that oral health status in HIV children deteriorated with the decline in CD4 counts. It should be noted that regular dental care in HIV infected individuals result in better oral health with no greater cost than regular attendance (Hastreiter and Jiang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health care is an important component of all round care for people with HIV infection. [ 17 ] The lack of healthy, functioning dentition can adversely affect the quality of life, complicate the management of medical conditions, and create or exacerbate nutritional and psychosocial problems. [ 18 ] Some antiretroviral drugs are sucrose-based in the form of a syrup or suspension such as Zidovudine and others may lead to decreased salivation, which makes them potentially cariogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is an important component of all‐round care for people with HIV infection . The lack of healthy, functioning dentition can adversely affect quality of life, complicate the management of medical conditions, and create or exacerbate nutritional and psychosocial problems .…”
Section: Discussionmentioning
confidence: 99%